Examination Stress and OSCE Performance in Basic Clinical Skills: A Study Among Medical Students - Maulana Nur Zaka; Rukman Abdullah; Rita Mustika (Media Publikasi Cendekia Indonesia, 2026)
The prevalence of stress among medical students has been reported to be 31.7% across six universities in Sudan and 58% at Andalas University. Academic stress is known to affect students’ performance, including failure in the Objective Structured Clinical Examination (OSCE). This study aimed to examine the relationship between examination-related stress levels and OSCE passing outcomes in the Basic Clinical Skills (KKD) module among students of the Faculty of Medicine, Universitas Sultan Ageng Tirtayasa. This study employed an observational analytic design with a cross-sectional approach. The study participants were third- and fourth-year medical students, totaling 92. Examination stress levels were measured using the Westside Anxiety Test Scale, while OSCE passing status was obtained from secondary academic records. Bivariate analysis was conducted using the chi-square test. The most commonly reported level of examination stress was moderate (47.6%), followed by severe (37.0%) and mild (16.3%). The highest failure rate was observed in the BCS-OSCE 3 (23.9%), followed by BCS-OSCE 2 (10.9%) and BCS-OSCE 1 (7.6%). Bivariate analysis showed no significant association between examination stress levels and OSCE KKD passing status. Similarly, no significant relationship was found between daily study duration and OSCE passing outcomes.